Caring for a stroke patient: The burden and experiences of primary caregivers in Uganda - A qualitative study - Namale Gertrude; Rachel Kawuma; Winifred Nalukenge; Onesmus Kamacooko; Laetitia Yperzeele; Patrick Cras; Edward Ddumba; Robert Newton; Janet Seeley (Wiley, 2019)
Abstract Aim We assessed the burden and experiences of caregivers looking after stroke patients in Kampala, Uganda. Design We conducted a qualitative cross‐sectional study between May 2018-July 2018 among primary caregivers of stroke patients. Methods The primary caregiver was defined as the person spending most of the time providing daily care for the stroke patient for at least four months. Purposive sampling was used to consecutively recruit the primary caregivers. In‐depth interviews were conducted, and audiotape recorded, and observations were also made. Data were managed using NVIVO 12.0 following thematic approach. Results Twenty‐five caregivers were included in the analysis with a mean age of 39.3, SD 10.7. Four themes were identified from the qualitative analysis on caregivers' experiences of looking after stroke patients: taking on new responsibilities, factors that protected caregivers from breaking down, limited resources and experiences with patient outcomes. Our findings highlight the need for interventions to support stroke patients and their caregivers.